Increased risk of hospital admission for mood disorders following admission for epilepsy. (28th August 2018) - Kim, Anna M.; Rossi, Kyle C.; Jetté, Nathalie; Yoo, Ji Yeoun; Hung, Kenneth; Dhamoon, Mandip S.
Abstract : Objective: To determine if epilepsy admissions, compared to admissions for other medical causes, are associated with a higher readmission risk for mood disorders. Methods: The Nationwide Readmissions Database is a nationally representative dataset comprising 49% of US hospitalizations in 2013. In this retrospective cohort study, we used ICD-9-CM codes to identify medical conditions. Index admissions for epilepsy (n = 58, 278) were compared against index admissions for stroke (n = 215, 821) and common medical causes (n = 973, 078). Readmission rates (per 100, 000 index admissions) for depression or bipolar disorders within 90 days from discharge for index hospitalization were calculated. Cox regression was used to test for associations between admission type (defined in 3 categories as above) and readmission for depression or bipolar disorder up to 1 year after index admission, in univariate models and adjusted for age, sex, psychiatric history, drug abuse, income quartile of patient's zip code, and index hospitalization characteristics. Results: The adjusted hazard ratio (HR) for readmission for depression in the epilepsy group was elevated at 2.80 compared to the stroke group (95% confidence interval [CI] 2.39–3.27, p < 2 × 10 −16 ), and 2.09 compared to the medical group (95% CI 1.88–2.32, p < 2 × 10 −16 ). The adjusted HR for readmission for bipolar disorder in the epilepsy group was elevated at 5.84 compared to the stroke group (95% CI 4.56–7.48, p < 2 × 10 −16 ), and 2.46 compared to the medical group (95% CI 2.16–2.81, p < 2 × 10 −16 ). Conclusion: Admission for epilepsy was independently associated with subsequent hospital readmission for mood disorders. The magnitude of elevated risk in this population suggests that patients admitted with epilepsy may warrant targeted psychiatric screening during their hospital admission.